Influence of the modifying physical fields on a structure and rheological properties composition motor oils - Аулін, В.В. (Problems of Tribology, 2014)
The theoretical ground of change of structure is conducted and rheological properties of composition motor oils at treatment the physical fields with the use of model of Einstein for the dispersive medium.